An Anti‐CD147 Antibody−Drug Conjugate Mehozumab‐DM1 is Efficacious Against Hepatocellular Carcinoma in Cynomolgus Monkey - Wan Huang; Liping Zhong; Ying Shi; Qingzhi Ma; Xiangmin Yang; Hongmei Zhang; Jing Zhang; Ling Wang; Kun Wang; Jingzhuo Li; Jie Zou; Xu Yang; et al. (Advanced Science)
Abstract Effective treatment strategies are urgently needed for hepatocellular carcinoma (HCC) patients due to frequent therapeutic resistance and recurrence. Antibody‐drug conjugate (ADC) is a specific antibody‐drug conjugated with small molecular compounds, which has potent killing activity against cancer cells. However, few ADC candidates for HCC are undergoing clinical evaluation. CD147 is a tumor‐associated antigen that is highly expressed on the surface of tumor cells. Here CD147 is found significantly upregulated in tumor tissues of HCC. Mehozumab‐DM1, a humanized anti‐CD147 monoclonal antibody conjugated with Mertansine (DM1) is developed. Mehozumab‐DM1 is effectively internalized by cancer cells and demonstrated potent antitumor efficacy in HCC cells. In vivo evaluation of Mehozumab‐DM1 is conducted in a CRISPR‐mediated PTEN and TP53 mutation cynomolgus monkey liver cancer model, which is poorly responsive to sorafenib treatment. Mehozumab‐DM1 demonstrated potent tumor inhibitory efficacy at doses of 0.2 and 1.0 mg kg−1 treatment groups in cynomolgus monkey. No treatment‐related adverse reactions or body weight loss are observed. Interestingly, Mehozumab‐DM1 treatment induced RIPK‐dependent tumor cell necroptosis through inhibiting IκB kinase/NF‐κB pathway. In conclusion, Mehozumab‐DM1 potently inhibits hepatoma through effective internalization to release payload and inducing cell necroptosis to enhance the bystander effect, which is a promising treatment for refractory HCC.